Le savoir technique dans l’art de peindre au Moyen Âge : les modes opératoires décrits dans le Liber Diversarum Artium (MS. H277, bibliothèque de l’école de médecine de Montpellier) - Anne Leturque (In Situ)
The interest for mediaeval pictorial techniques can be analysed through the study of the paintings, the observation of the techniques used as well as the testing of those techniques but also with the support of written sources like notarial acts or, concerning our work, records of paint formulas. In 2011, Mark Clarke published a new version of the Liber Diversarum Aritum initial text and it has been chosen as a support for the argument. This unexpected publication, issued only a few months after the beginning of our research allowed us to work on aspects which were not offered in the more conventional philological approach. As a consequence we decided to elaborate our thought on the analysis of the methods that are developed in the text. We did not leave out the translation of this text neither the concrete analysis of the manuscript nor its dating but we do not wish to make it the main point of our process. The information we find in the Liber of Montpellier can be organised according to the five main principles the painter follows to paint: the drawing, the creation of colours, their mixing, the use of colours in painting, the silver and gold decoration. Associated to this modus operandi is a concern for the quality of the support, its preparation and the precaution which are essential for the application of the materials and tools. We shall expand on some of those details. The comparisons made with preserved mediaeval works shall help to determine what distance unifies and separates theory from practise. Thanks to this work on the analysis of the technique, we hope to contribute to a larger reflection persisting on the skills developed by the mediaeval painter.